2012
DOI: 10.1590/s1677-04202012000100008
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and antioxidant activity in Jatropha curcas L. under salt stress

Abstract: Biodiesel is an alternative to petroleum diesel fuel. It is a renewable, biodegradable, and nontoxic biofuel. Interest in the production of biodiesel from Jatropha curcas L. seeds has increased in recent years, but the ability of J. curcas to grow in salt-prone areas, such as the Caatinga semiarid region, has received considerably meager attention. The aim of this study was to identify the main physiological processes that can elucidate the pattern of responses of J. curcas irrigated with saline water, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 66 publications
10
31
0
Order By: Relevance
“…Kumar et al (2008) also found decreased protein content in J. curcas callus under 100 mM of NaCl; their findings corroborate the results in the present study. These results also corroborate other studies, such as that by Campos et al (2012), who found decreased protein levels in J. curcas plants grown under saline conditions.…”
Section: Morphologicalsupporting
confidence: 93%
See 4 more Smart Citations
“…Kumar et al (2008) also found decreased protein content in J. curcas callus under 100 mM of NaCl; their findings corroborate the results in the present study. These results also corroborate other studies, such as that by Campos et al (2012), who found decreased protein levels in J. curcas plants grown under saline conditions.…”
Section: Morphologicalsupporting
confidence: 93%
“…Our study showed that moderate salinity levels (EC 1.76 dS.m -1 ) did not affect the amino acid, proline and carbohydrate; they were only affected by higher salt concentrations. However, Campos et al (2012) found increased osmolyte levels in J. curcas plants cultivated in higher salt concentration (EC, 3.5 dS m -1 ) in the irrigation water. Contradictory results about J. curcas seedlings were recorded by Díaz-López et al (2012), who did not find any contribution from the osmotic adjustment resulting from osmolytes accumulation when plants were under salt stress.…”
Section: Morphologicalmentioning
confidence: 84%
See 3 more Smart Citations